Nanocatalysis: Synthesis and Applications - Polshettiwar V. Vivek; Asefa T. Tewodros (Hoboken, Wiley, 2013)
This book reviews the synthetic applications of nanomaterials as catalysts, with the chapters emphasizing both catalytic performance and the synthesis and characterization of nanocatalysts. The reactions and processes covered show the relevance of nanocat.